Year in Review, Public Anthropology, 2013: Webs of Meaning, Critical Interventions. Issue 2 (9th May 2014) - Benson, Peter
ABSTRACT In this essay, I provide an overview of public anthropology from the year 2013, examining how anthropologists engaged public, socially relevant issues and brought anthropological understandings and expertise into public debates, conversations, and forums. In particular, I focus on the ways that the publication of anthropology is changing to reflect trends toward open‐access electronic publishing and new formats for scholarly and public discussion. I then highlight how anthropologists engaged with a set of specific issues and topics, including debates about same‐sex marriage in the United States; the trial of Efraín Ríos Montt, the former dictator of Guatemala who was tried and convicted of genocide last year; and the publication of a controversial new memoir by the anthropologist Napoleon Chagnon. Taken together, the sections of this essay disclose the significant ways that anthropologists have engaged with and contributed to public debates and contested issues.